2020
DOI: 10.1186/s12894-020-00726-y
|View full text |Cite
|
Sign up to set email alerts
|

Prostate artery embolization has long term efficacy for treatment of severe lower urinary tract symptoms from giant prostatic hyperplasia

Abstract: Background Patients with severe lower urinary tract symptoms (LUTS) from giant prostatic hyperplasia (GPH): prostate volume greater than 200 mL that do not respond to medical therapy may not be eligible for surgical treatments due to morbidities, technical challenges, and patient preference. This retrospective investigation examined the long-term efficacy and safety of prostatic arterial embolization (PAE) as a treatment option for severe LUTS due to GPH in a large patient cohort. Methods Of 529 patients who… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
(132 reference statements)
0
5
0
2
Order By: Relevance
“…In cases of patients with large prostates, enucleation procedures such as holmium laser enucleation of the prostate should be considered as an alternative to TURP or open prostatectomy, although laser enucleation procedures have the main drawback of a long learning curve and require specific endourological equipment which is not available in all institutions [6,31,32]. However, PAE has been reported to be a safe and efficacious treatment in patients with prostate volumes of up to 100 mL or larger [33,34]. However, PAE has been reported to be a safe and effective treatment in patients with prostate volumes of up to 100 mL or larger that can be performed under local anaesthesia in patients with associated cardioulmonary comorbidities; therefore, PAE might be reserved for those patients with larger prostates and those not suitable for procedures requiring general anaesthesia such as TURP or enucleation techniques [31].…”
Section: Discussionmentioning
confidence: 99%
“…In cases of patients with large prostates, enucleation procedures such as holmium laser enucleation of the prostate should be considered as an alternative to TURP or open prostatectomy, although laser enucleation procedures have the main drawback of a long learning curve and require specific endourological equipment which is not available in all institutions [6,31,32]. However, PAE has been reported to be a safe and efficacious treatment in patients with prostate volumes of up to 100 mL or larger [33,34]. However, PAE has been reported to be a safe and effective treatment in patients with prostate volumes of up to 100 mL or larger that can be performed under local anaesthesia in patients with associated cardioulmonary comorbidities; therefore, PAE might be reserved for those patients with larger prostates and those not suitable for procedures requiring general anaesthesia such as TURP or enucleation techniques [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, the large prostate size group had significantly better outcomes compared to the medium prostate group with regards to IPSS, maximum flow rate (Q max ), PV and PVR. Several authors consider PAE to be better suited for larger prostates (>80 g) as it may be more technically amenable to embolization and more likely to have favorable results compared to smaller prostates (<50 g) [ 28 , 47 , 48 ]. Other studies have shown little correlation with prostate size and clinical outcome; one retrospective study evaluated prostate size prior to PAE in order to determine its impact on IPSS score.…”
Section: Pre-procedural Patient Evaluationmentioning
confidence: 99%
“…Open simple prostatectomy and novel endoscopic holmium laser enucleation (HoLEP) is the recommendation for glands >100cc [4]. Simple open prostatectomy is associated with signi cant morbidity in this setting, including peri-operative blood loss requiring transfusion (8-15%), urinary incontinence (10%) and urinary bladder neck stenosis or urethral strictures (5%) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Giant prostatic hyperplasia (GPH), also known as megaprostate, has been de ned as BPH prostatomegaly with gland volume greater than 200cc [7]. Previously, GPH was de ned as gland weight over 500g post resection [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation